Automation of pilot-scale open raceway pond: A case study of CO2-fed pH control on Spirulina biomass, protein and phycocyanin production. (October 2019) - Mehar, Jitendra; Shekh, Ajam; M. U., Nethravathy; Sarada, R.; Chauhan, Vikas Singh; Mudliar, Sandeep
Highlights: Indigenous automation system for microalgae cultivation developed. Equipped with CO2 fed pH control and membrane sparger. Temperature, pH, DO, Light can be recorded automatically. Pilot scale Spirulina cultivation using automated CO2 fed pH control. Maximum biomass, protein and C-Phycocyanin was obtained at pH 8.5. Abstract: Spirulina is known to produce high protein and phycocyanin of commercial importance with concomitant CO2 utilisation. The pH is one of the most important factors for cell growth, CO2 utilisation and controlling contamination. In this study, an indigenously developed automated system for Spirulina cultivation was used at pilot scale, where CO2 supply was aimed to provide carbon source and to control culture pH. Among all the studied pH (7.5 ± 0.1, 8.5 ± 0.1, 9.5 ± 0.1), pH 8.5 was found to be the best where biomass productivity, CO2 bio-fixation rate, protein and phycocyanin content were noted as 72 mg L −1 d -1, 0.13 g L -1 d -1, 64%, and 14%, respectively. Though the culture at pH 9.5 experienced late CO2 feeding, it was healthy and showed almost similar metabolite content compared to pH 8.5. The pilot scale automation system developed here can be employed to enhance CO2 fed pH control based performance of Spirulina or any microalgae cultivation.